Overview of systematic reviews and meta-analyses assessing the predictability and clinical effectiveness of clear aligner therapy - Abdulraheem Alwafi; Yashodhan M. Bichu; Ariga Avanessian; Samar M. Adel; Nikhilesh R. Vaid; Bingshuang Zou (Elsevier, 2023)
This study conducted an overview of systematic reviews (SRs) and included randomized controlled trials (RCTs) to evaluate the predictability of tooth movements and clinical effectiveness of clear aligner therapy (CAT) compared to fixed appliances (FAs). The PRISMA guidelines were followed, and seven electronic databases were systematically searched for publications up to March 15, 2022. The quality of the included SRs and RCTs was assessed using the AMSTAR-2 and RoB-2 tools, respectively. Initially, 18 SRs and 2 RCTs were identified, and after quality assessments, 11 SRs and 1 RCT were retained for data synthesis. The comparison between software-predicted and actual tooth movements indicated that CAT's accuracy in predicting rotational movements, especially for canines, was not reliable. Horizontal movements, particularly in the upper incisors, were more predictable, while vertical movements were less predictable. The overall American Board of Orthodontics (ABO) objective grading system (OGS) scores did not show a significant difference between the CAT and FAs groups, with a high heterogeneity of 90 % (P < 0.0001) and a confidence interval of -2.32 to 18.4. The current evidence level regarding the predictability of tooth movements and clinical effectiveness of CAT compared to conventional FAs is considered to be low to moderate. While CAT can be used for treating complex malocclusions, it tends to yield less accurate results than FAs.